The Liquid Mirror (Transcending Aesthetic Utopianism in Nabokov’s Invitation to a Beheading and The Gift) - Mikola, Gyöngyi (SlavVaria, 2023)
Nabokov wrote his masterpiece Invitation to a Beheading interrupting his own work, writing another novel, The Gift. My hypothesis is that Invitation to a Beheading can be considered as a solution of a problem or elaboration of an idea, which was arisen during the creation of the other, the “main” book. In the present paper research I analyze the water motifs of the Invitation.. and The Gift with close reading method to demonstrate the relationship of Nabokovian reader and/or writer heroes to the art of literature, and, besides, realization of self-mimetic, self-reflective potentialities of literature as specific liquid mirror in these novels. I collate the liquid mirror concept with the parodic representations of the utopianism of Russian aesthetic tradition, first of all with Nikolay Chernyshevsky’s materialist utopia. I also study the relevance of Nietzschean concept of aesthetic redemption in connection with Nabokovian novels, and I suggest a special, synchronous, simultaneous idea of this philosophical term: in my opinion Nabokovian aesthetic redemption is confined only to the duration of writing or reading. But this real, empirical time of literary process works as a gap, transforms to a secret passage, a way through to the unknown, timeless outside.